(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
The relentless pursuit of knowledge and continuous learning is essential to keep any field of science relevant and applicable to the needs of society. The same is applicable to Ayurveda. In Ayurveda, Caraka Samhita recognized the importance of Pratisamskarana as a tool for updating earlier literature. Pratisamskarana includes the elaboration of portions those are brief and unclear, summarisation of those which are elaborate, thus making a new version of the original. This strong tradition of Pratisamskarana was already prevalent during the Samhita-kala. Ashtanga Hridaya, the third major treatise on Ayurveda, acknowledges that it has collected and presented the essence of knowledge from earlier textbooks. In order to establish “Ashtanga Hridaya is the Pratisamskrita version of Brihatrayi”, the technique of Panchavaya vakya was employed to establish a statement. Panchavaya vakya as described in the Nyaya system and included in the 44 Vadamarga by Acarya Caraka contains five components -Pratijna, Hetu, Udhaharana, Upanaya, Nigamana. A literary study has been done to understand Pratisamskarana, and to compare the detailed and concise portion of Caraka Samhita and Susruta Samhita with the later text in Samhita kala, Ashtanga Hridaya. This attempt aims to establish that the Ashtanga Hridaya is an updated version of Brihatrayi, based on the analysis through Panchavaya vakya.